Multi‐model analysis of Northern Hemisphere winter blocking: Model biases and the role of resolution. Issue 10 (20th May 2013) - Anstey, James A.; Davini, Paolo; Gray, Lesley J.; Woollings, Tim J.; Butchart, Neal; Cagnazzo, Chiara; Christiansen, Bo; Hardiman, Steven C.; Osprey, Scott M.; Yang, Shuting
Abstract : [1] Blocking of the tropospheric jet stream during Northern Hemisphere winter (December‐January‐February) is examined in a multi‐model ensemble of coupled atmosphere‐ocean general circulation models (GCMs) obtained from the Coupled Model Intercomparison Project Phase 5 (CMIP5). The CMIP5 models exhibit large biases in blocking frequency and related biases in tropospheric jet latitude, similar to earlier generations of GCMs. Underestimated blocking at high latitudes, especially over Europe, is common. In general, model biases decrease as model resolution increases. Increased blocking frequency at high latitudes in both the Atlantic and Pacific basins, as well as more realistic variability of Atlantic jet latitude, are associated with increased vertical resolution in the mid‐troposphere to lowermost stratosphere. Finer horizontal resolution is associated with higher blocking frequency at all latitudes in the Atlantic basin but appears to have no systematic impact on blocking near Greenland or in the Pacific basin. Results from the CMIP5 analysis are corroborated by additional controlled experiments using selected GCMs. Key Points: CMIP5 models have large blocking biases and associated jet biases Increased spatial resolution is associated with reduced blocking and jet biases Vertical and horizontal resolution give blocking changes in different regions